Novel set of real-time PCR primers for simultaneous detection of Liberibacter species associated with citrus Huanglongbing (Scientia Agricola, 2015)
Huanglongbing (HLB), a devastating citrus disease caused by the bacterium “Candidatus Liberibacter spp.”, is now responsible for significant economic losses worldwide. Yet, no effective disease control has been found, and the non-cultivability of the bacterium has severely hampered studies on the pathogen. The 16S rDNA gene is a well-characterized sequence, essential for cell survival, and is used for bacterial identification or assignment of close relationships at the genus and species levels. Quantitative Real-Time PCR (qPCR) assays based on 16S rDNA genes are widely used in the detection of “Ca. Liberibacter spp.” in multiplex reactions. We have developed for the first time a set of qPCR primers based on the conserved 16S rDNA gene, which specifically and simultaneously detects in a singleplex reaction, all three bacterial species associated with HLB, and can differentiateCa.Liberibacter asiaticus or africanus from americanus by their characteristic melting curves. The assay is very sensitive, and it was possible to amplify expected DNA fragments with an efficiency of 98 % using the Syber Green system and a Ct value lower than tested methods for HLB diagnosis. The application of this fast, simple and efficient detection methodology could also be important in the detection of all species of HLB-associated Liberibacters and could contribute to early pathogen detection, a crucial step in the development of preventive strategies aimed at avoiding the dissemination of this devastating disease in HLB-free areas.